Pemberdayaan Masyarakat Melalui Peran BMT UGT Nusantara Dalam Melatih Manajemen Keuangan Terhadap Produk Tabungan Tampan (Tabungan Masa Depan) - merna, mernawati; Muhammad Romli Muar (Universitas Islam Negeri Mataram, 2024)
This activity aims to determine the quality of financial literacy in the Sumbermanjing Wetan area community regarding money management with future savings products (MAPAN) so that the increasingly diverse customer needs are also accompanied by intense competition, encouraging BMT UGT Nusantara Sumbermanjing Wetan branch to increase customer interest. Of course, using sharia principles with a mudharabah musyarakah agreement, where the hope is that the benefits obtained can help in the expected future. The methods used in this research are observation and documentation. In the sharia financial system and Baitul Malwadhamil BMT, the profit sharing model only applies to business participation or business collaboration agreements.